2019
DOI: 10.56109/aup-sna.v9i1.61
|View full text |Cite
|
Sign up to set email alerts
|

Diversité floristique et connaissances des usages rituels et médico-magiques des espèces végétales dans la ville de Cotonou, Bénin

Abstract: La communauté scientifique africaine prend de plus en plus conscience de la valeur de la médecine traditionnelle et de la nécessité d’améliorer les connaissances sur les différentes facettes de cette médecine. Cette étude s'intéresse à l’utilisation des plantes à des fins rituelles et médico-magiques et, a pour objectif de recenser les plantes à usage rituels et médico-magique et d’évaluer les connaissances des populations urbaines en relation avec ces plantes. Les travaux se sont déroulés dans la ville de Cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Different studies carried out in several regions of the world have also reported the same categories of uses for woody species (Dossou et al 2012;Sop et al 2012;Moteetee et al 2019;Ouédraogo et al 2019;Mapaya et al 2022). More particularly, the use of plant species for medico-magical purposes is a common trend in certain African countries (Sop et al 2012;Lougbegnon 2019;Dossou-Yovo et al 2021;Gbesso et al 2021), South-America (Paiva de Lucena et al 2012;Alonso-Castro et al 2019), Asia (Ernst et al 2015) and European region (Mateji et al 2020). The PCA mentioned 22 woody species most frequently used by local populations for all of the identified use categories.…”
Section: Endogenous Knowledge and Uses Of Woody Plantsmentioning
confidence: 85%
“…Different studies carried out in several regions of the world have also reported the same categories of uses for woody species (Dossou et al 2012;Sop et al 2012;Moteetee et al 2019;Ouédraogo et al 2019;Mapaya et al 2022). More particularly, the use of plant species for medico-magical purposes is a common trend in certain African countries (Sop et al 2012;Lougbegnon 2019;Dossou-Yovo et al 2021;Gbesso et al 2021), South-America (Paiva de Lucena et al 2012;Alonso-Castro et al 2019), Asia (Ernst et al 2015) and European region (Mateji et al 2020). The PCA mentioned 22 woody species most frequently used by local populations for all of the identified use categories.…”
Section: Endogenous Knowledge and Uses Of Woody Plantsmentioning
confidence: 85%